FOXO3 regulates a common genomic program in aging and glioblastoma stem cells. Issue 4 (18th December 2021) - Audesse, Amanda J.; Karashchuk, Galina; Gardell, Zachary A.; Lakis, Nelli S.; Maybury‐Lewis, Sun Y.; Brown, Abigail K.; Leeman, Dena S.; Teo, Yee Voan; Neretti, Nicola; Anthony, Douglas C.; Brodsky, Alexander S.; Webb, Ashley E.
Abstract: Background: Glioblastoma (GBM) is an aggressive, age‐associated malignant glioma that contains populations of cancer stem cells. These glioma stem cells (GSCs) evade therapeutic interventions and repopulate tumors due to their existence in a slowly cycling quiescent state. Although aging is well known to increase cancer initiation, the extent to which the mechanisms supporting GSC tumorigenicity are related to physiological aging remains unknown. Aims: Here, we investigate the transcriptional mechanisms by which Forkhead Box O3 (FOXO3), a transcriptional regulator that promotes healthy aging, affects GSC function and the extent to which FOXO3 transcriptional networks are dysregulated in aging and GBM. Methods and results: We performed transcriptome analysis of clinical GBM tumors and observed that high FOXO3 activity is associated with gene expression signatures of stem cell quiescence, reduced oxidative metabolism, and improved patient outcomes. Consistent with these findings, we show that elevated FOXO3 activity significantly reduces the proliferation of GBM‐derived GSCs. Using RNA‐seq, we find that functional ablation of FOXO3 in GSCs rewires the transcriptional circuitry associated with metabolism, epigenetic stability, quiescence, and differentiation. Since FOXO3 has been implicated in healthy aging, we then investigated the extent to which it regulates common transcriptional programs in aging neural stem cells (NSCs) and GSCs. We uncover a shared transcriptional program and, most strikingly, find that FOXO3‐regulated pathways are associated with altered mitochondrial functions in both aging and GBM. Conclusions: This work identifies a FOXO‐associated transcriptional program that correlates between GSCs and aging NSCs and is enriched for metabolic and stemness pathways connected with GBM and aging.